Efforts To Improve Civics Education Learning Achievement Through Learning Method C Ooperatif Model Stad (Student Teams Achievement Division) In Class Student Of X Sm A Negeri 2 Sutera Year Lesson 2016 - Sofyan Sofyan (Jurnal Ilmiah Pendidikan Scholastic, 2017)
Learning activities together can help stimulate active learning. Teaching and learning in the classroom is to stimulate active learning, but the ability to teach through small group collaborative activities will allow to promote active learning activities in a special way. What was discussed student with his friends and what it teaches students to his friends allows them to gain an understanding and mastery of subject matter. This study is based on the problem: (a) How can increase learning achievement Civics with the implementation of cooperative learning method STAD model? (B) How will the cooperative learning method on motivation to learn civics ?. While the purpose of this study was: (a) Want to know Civics increase learning achievement after the implementation of cooperative learning. (B) Want to know the effect of motivation to learn civics after the implementation of cooperative learning. (C) provide an overview of appropriate learning methods in an effort to improve student achievement and make students actively in learning activities. This study uses action research (action research) three rounds. each round consists of four stages: design, activity and observation, reflection, and refisi. Goal of this research is class X BC A Negeri 2 Sutera in the school year 20 16 /20 17 . Data obtained in the form of a formative test results, observation sheet teaching and learning activities. From the analysis we found that student achievement increased from the first cycle to the third cycle, the first cycle (68.42%), the second cycle (81.58%), the third cycle (94.74%). Conclusions from this research is cooperative learning methods can be a positive influence on students' motivation achievement and class X SM A Negeri 2 Sutera Year Lesson 20 16/2017 and this model can be used as an alternative civics lesson.